Relative efficacy of cash versus vouchers in engaging opioid substitution treatment clients in survey-based research. Issue 4 (12th December 2012) - Topp, Libby; Islam, M Mofizul; Day, Carolyn Ann
Abstract : Concerns that cash payments to people who inject drugs (PWID) to reimburse research participation will facilitate illicit drug purchases have led some ethical authorities to mandate department store/supermarket vouchers as research reimbursement. To examine the relative efficacy of the two forms of reimbursement in engaging PWID in research, clients of two public opioid substitution therapy clinics were invited to participate in a 20–30 min, anonymous and confidential interview about alcohol consumption on two separate occasions, 4 months apart. Under the crossover design, at Time 1, clients of Clinic 1 were offered $A20 cash as reimbursement, while clients of Clinic 2 were offered an $A20 voucher; at Time 2, the form of reimbursement was reversed. Using clinic records to determine the denominator (number of clients dosed), we found that compared with clients offered a voucher, a significantly higher proportion of clients who were offered cash participated in the survey (58% (139/241) vs 74% (186/252); χ 2 =14.27; p=0.0002). At first participation, respondents most commonly reported planning to purchase food/drinks/groceries (68%), cigarettes (21%) and transport/fuel (11%) with their payments, with those reimbursed in cash more likely to report planning to fund transport/fuel (19% vs 1%; p<.01) and less likely to report planning to purchase food/drinks/groceries (62% vs 76%; p=0.02). Just three out of 155 cash participants reported planning to purchase illicit drugs with their payment. Results demonstrate that modest cash payments enhanced recruitment of this group, an important consideration given the challenges of delineating the parameters of a population defined by illegal activity, seemingly without promoting excessive additional drug use.